A systematic review of the relation between self‐compassion and depressive symptoms in adolescents. (26th June 2019) - Pullmer, Rachelle; Chung, Jason; Samson, Lindsay; Balanji, Sherene; Zaitsoff, Shannon
ABSTRACT: Research on self‐compassion and depressive symptoms is growing at an exponential pace. This systematic review provides an in‐depth exploration of the relation between self‐compassion and depressive symptoms in adolescents. In accordance with PRISMA guidelines, MEDLINE, CINAHL, and PsycINFO databases were systematically searched and 18 studies were identified. Results demonstrate the potentially pertinent role that self‐compassion may play in the development, maintenance, and treatment of depression in adolescents, yet reflect on the paucity of research on this topic with respect to mechanisms of change. These studies further highlight how the impact of self‐compassion may differ according to gender and age and underscore the need to account for other diversity‐related variables, such as ethnic‐racial group, socioeconomic status, and sexual orientation. Despite such limitations in the literature, the current findings extend research in adults by providing support for the relevance of self‐compassion in adolescence, particularly with respect to the prevention of depressive symptoms.